IMPACT OF ACTIVE SURVEILLANCE SCREENING OF MRSA ON SURGICAL SITE INFECTION RATES- A PROSPECTIVE INTERVENTIONAL STUDY - Fatima, Tazeen; Rezwan, Faiza; Ali, Farheen; Luxmi, Shobha; Raheel, Furqan Ahmed; Muhmmad Nadeem (Infectious Diseases Journal of Pakistan, 2023)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most common cause of surgical site infections. Different methods are employed to reduce nosocomial spread including application of Isolation precautions, admission screening cultures and MRSA decolonization 3,4,5,6,7. Preoperative MRSA screening in patients undergoing cardiac surgeries can reduce the risk of surgical site infections. To evaluate the significance of preoperative MRSA screening on rates of surgical site infections in cardiac surgery patients Material and Methods: This was a prospective interventional study, conducted at the National Institute of Cardiovascular diseases, Karachi from 1st February 2022- 31st July 2022. Preoperative MRSA screening in patients undergoing cardiac surgeries was performed at the Microbiology Laboratory. Patients identified as colonized were isolated and decolonized with chlorhexidine baths prior to surgeries. Surgical site infections (SSIs) rates were recorded by Infection control nurse through active surveillance for the screening period. SSI rates for a prescreening period of 6 months (August 2021- January 2022) was retrieved through electronic medical records for comparison. Results: Total 359 patients were screened from 1st February 2022- 31st July 2022, out of which 20 were colonized with MRSA. None of the patients who screened positive for MRSA developed SSI. 11 SSIs with MRSA were reported from August 2021- January 2022 and 4 SSIs were reported from February 2022-July 2022 (p value < 0.05). Conclusion: It can be concluded that active MRSA screening and subsequent implementation of decolonization policy would decrease the percentage of SSI in cardiac surgery Keywords: MRSA, Screening, Surgical site infection, Surveillance